BCL-2 protein family: attractive targets for cancer therapy - Deeksha Kaloni; Sarah T Diepstraten; Andreas Strasser; Gemma L Kelly (Apoptosis, 2023)
Acquired resistance to cell death is a hallmark of cancer. The BCL-2 protein family members play important roles in controlling apoptotic cell death. Abnormal over-expression of pro-survival BCL-2 family members or abnormal reduction of pro-apoptotic BCL-2 family proteins, both resulting in the inhibition of apoptosis, are frequently detected in diverse malignancies. The critical role of the pro-survival and pro-apoptotic BCL-2 family proteins in the regulation of apoptosis makes them attractive targets for the development of agents for the treatment of cancer. This review describes the roles of the various pro-survival and pro-apoptotic members of the BCL-2 protein family in normal development and organismal function and how defects in the control of apoptosis promote the development and therapy resistance of cancer. Finally, we discuss the development of inhibitors of pro-survival BCL-2 proteins, termed BH3-mimetic drugs, as novel agents for cancer therapy.